Discrimination between Mycoplasma mycoides subsp. capri and Mycoplasma capricolum subsp. capricolum using PCR-RFLP and PCR. Issue 3 (September 2015) - Cillara, Grazia; Manca, Maria Giovanna; Longheu, Carla; Tola, Sebastiana
Highlights The housekeeping dld gene was proposed in this study for detecting all mycoplasmas belonging to the 'M. mycoides' cluster. Mycoplasma mycoides subsp. capri (Mmc) was differentiated from Mycoplasma capricolum subsp. capricolum (Mcc) by PCR-RFLP. A new single tube PCR was developed in this study. PCR-RFLP and PCR provide rapid and useful assays in routine diagnosis.